Combination of phenolic profiles, pharmacological properties and in silico studies to provide new insights on Silene salsuginea from Turkey. (December 2018) - Zengin, Gokhan; Rodrigues, Maria João; Abdallah, Hassan H.; Custodio, Luisa; Stefanucci, Azzurra; Aumeeruddy, Muhammad Zakariyyah; Mollica, Adriano; Rengasamy, Kannan R.R.; Mahomoodally, Mohamad Fawzi
Graphical abstract: Highlights: Biochemical fingerprints of Silene salsuginea extracts were evaluated. Antioxidant, enzyme inhibitory and anti-inflammatory effects were investigated. In silico studies were performed for providing further insights. Epicatechin, (+)-catechin and kaempferol showed the highest binding affinity towards the studied enzymes in silico . S. salsuginea may be considered as natural source of biologically-active compounds for phyto-pharmaceuticals. Abstract: The genus Silene is renowned in Turkey for its traditional use as food and medicine. Currently, there are 138 species of Silene in Turkey, amongst which have been several studies for possible pharmacological potential and application in food industry. However, there is currently a paucity of data on Silene salsuginea Hub.-Mor. This study endeavours to access its antioxidant, enzyme inhibitory, and anti-inflammatory properties. Besides, reversed-phase high-performance liquid chromatography-diode array detector (RP-HPLC-DAD) was used to detect phenolic compounds, and molecular docking was performed to provide new insights for tested enzymes and phenolics. High amounts of apigenin (534 μg/g extract), ferulic acid (452 μg/g extract), p -coumaric acid (408 μg/g extract), and quercetin (336 μg/g extract) were detected in the methanol extract while rutin (506 μg/g extract) was most abundant in the aqueous extract. As for their biological properties, the methanol extract exhibited the best antioxidant effect in the DPPH and CUPRAC assays, and also the highest inhibition against tyrosinase. The aqueous extract was the least active enzyme inhibitor but showed the highest antioxidant efficacy in the ABTS, FRAP, and metal chelating assays. At a concentration of 15.6 μg/mL, the methanol extract resulted in a moderate decrease (25.1%) of NO production in lipopolysaccharide-stimulated cells. Among the phenolic compounds, epicatechin, (+)-catechin, and kaempferol showed the highest binding affinity towards the studied enzymes in silico . It can be concluded that extracts of S. salsuginea are a potential source of functional food ingredients but need further analytical experiments to explore its complexity of chemical compounds and pharmacological properties as well as using in vivo toxicity models to establish its maximum tolerated dose.